Operations Management, Sustainability & Industry 5.0: A critical analysis and future agenda - Garrido, Susana; Muniz, Jorge [UNESP]; Batista Ribeiro, Vagner [UNESP] (Elsevier, 2024)
This study aims to discuss how literature explores the relationship between Industry 4.0 and Industry 5.0, operations management, and sustainability. A systematic literature review was conducted to investigate this relationship, and 30 articles were identified. The data from these articles was discussed in a structured summary, which facilitated its analysis. It was identified that the Internet of Things (IoT) and Big Data are the most commonly cited technologies in the current literature. However, it was realised that most of the literature analysed in this study focuses mainly on Industry 4.0 instead of Industry 5.0. This represents a concern and also an empirical and theoretical opportunity for a deeper analysis of topics such as people, sustainability, and organizational resilience related to Operations Management & Supply Chain. These opportunities can provide insights and assist researchers in future operations management practices and further research.
Keywords: Circular economy; Industry 4.0; Industry 5.0; Sustainability; Sustainable development goals